2013
DOI: 10.1002/ggge.20221
|View full text |Cite
|
Sign up to set email alerts
|

Magma storage and ascent conditions beneath Pico and Faial islands (Azores archipelago): A study on fluid inclusions

Abstract: [1] In the islands of Faial and Pico (the Azores), fluid inclusions are hosted in megacrysts of olivine (Mg#80-88) and clinopyroxene (Mg#79-90) in highly porphyritic lavas and in mineral assemblages of ultramafic xenoliths. Rare inclusions are contained in olivine phenocrysts (Mg# < 80) and plagioclases in poorly porphyritic lavas. Trails of late-stage inclusions are predominant over isolated early-stage inclusions. Almost all inclusions are re-equilibrated and the trapped fluid consists of pure CO 2 (Tm from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 78 publications
8
58
0
Order By: Relevance
“…We suggest that extensive fractional crystallization is dominant in these large volcanic edifices compared to lavas from the submarine rift zones and subaerial fissure zones. This is in agreement with thermobarometric calculations from and Zanon and Frezzotti (2013), which have shown that rocks derived from fissure eruptions at the Capelo and Horta Fissure Zones have not stagnated significantly during their ascent from the mantle, whereas melts at the Caldeira Volcano have undergone polybaric fractional crystallization and stagnation at shallower crustal levels, leading to the formation of trachytes (Pimentel et al, 2015). The variability of most major elements, in particular K 2 O, and incompatible trace element ratios, (e.g., La/Yb, Nb/Zr) at a given MgO content (Figures 4, 5) however, cannot be explained by simple fractional crystallization and may rather be related to changes in mantle source composition or degree of partial melting, respectively (see below).…”
Section: Geochemical Relationship Between the Rift Zone Lavassupporting
confidence: 80%
See 1 more Smart Citation
“…We suggest that extensive fractional crystallization is dominant in these large volcanic edifices compared to lavas from the submarine rift zones and subaerial fissure zones. This is in agreement with thermobarometric calculations from and Zanon and Frezzotti (2013), which have shown that rocks derived from fissure eruptions at the Capelo and Horta Fissure Zones have not stagnated significantly during their ascent from the mantle, whereas melts at the Caldeira Volcano have undergone polybaric fractional crystallization and stagnation at shallower crustal levels, leading to the formation of trachytes (Pimentel et al, 2015). The variability of most major elements, in particular K 2 O, and incompatible trace element ratios, (e.g., La/Yb, Nb/Zr) at a given MgO content (Figures 4, 5) however, cannot be explained by simple fractional crystallization and may rather be related to changes in mantle source composition or degree of partial melting, respectively (see below).…”
Section: Geochemical Relationship Between the Rift Zone Lavassupporting
confidence: 80%
“…The morphological, structural and geochemical features on Faial have been subject of several detailed studies in the last two decades (Madeira, 1998;Pacheco, 2001;Matias et al, 2007;Hildenbrand et al, 2012;Zanon and Frezzotti, 2013;Di Chiara et al, 2014;Marques et al, 2014;Trippanera Pimentel et al, 2015). Lithospheric extension is a major feature influencing both the morphology and structure of volcanic units forming the island.…”
Section: Discussion the Formation Of The Volcanic Rift Zonesmentioning
confidence: 99%
“…This process can occur on timescales of days to hours 64 in some cases. Secondly, volatile components within MI can be partitioned between the melt and 65 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 inclusions by Mironov and Portnyagin (2011), Zanon and Frezzotti (2013), and Zanon and 110 Pimentel (2015). Note, however, that H + diffusion out of the MI may also promote formation of …”
Section: Introduction 43mentioning
confidence: 99%
“…The CO 2 degassing maps here presented are thus important tools that characterize the CO 2 emission in quiescent periods of activity and are important to identify future periods of reactivation. Besides, several studies performed in these islands (e.g., Madeira and Brum da Silveira, 2003;Hildenbrand et al, 2012;Zanon and Frezzotti, 2013;Trippanera et al, 2014) have highlighted the importance of the tectonic control on the plumbing systems of the volcanoes, and most of the main degassing areas are also tectonically controlled, what reinforces the need to integrate different geological studies to better understand the volcanic systems. On another hand, the location of some of the identified DDS close to inhabited areas highlights the need to identify hazardous CO 2 zones both for the existing and for future constructions.…”
Section: Discussionmentioning
confidence: 94%
“…Zanon and Frezzotti (2013) studied CO 2 -rich fluid inclusions at Faial and Pico islands and estimated different depths for magma ponding sites, which varied from 5.6 to 21.2 km. The intra-crustal ponding system of small size was proposed to be located beneath the Caldeira Volcano, in agreement with the depths obtained by the tomography studies.…”
Section: Volcanismmentioning
confidence: 99%